ANALISIS PENGARUH KINERJA KEUANGAN PEMERINTAHAN DAERAH TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA UTARA - Rahmah Azizah; Horas Bagas; Hagai Rensa; Jholant Bringg Luck Amelia Br Sinaga; Dearma Sariani Sinaga (JURNAL LENTERA BISNIS, 2025)
This study aims to explore the relationship between the fiscal performance of local governments and the rate of economic expansion in the North Sumatra region in the period 2020 to 2022. Economic growth is seen as a central parameter in measuring the economic progress of a region, while the effectiveness of regional financial management is believed to have a significant influence on these dynamics. This study explores a number of financial metrics including the fiscal autonomy index, the level of decentralization, budget efficiency measures, and the proportion of spending alignment, all of which are examined in the context of Gross Regional Domestic Product (GRDP) as a benchmark for economic development. From the data collected, Medan City shows variability in its economic growth after the COVID-19 pandemic, with growth reaching 4.71% in 2022, after previously experiencing a sharp decline in 2020. This research investigates whether these indicators have the ability to accelerate the regional economy, both individually and collectively. By utilizing a literature review approach and a construction concept that is based on the theoretical basis of regional finance, it is hoped that the findings of this study can reveal the essence of the vital role of fiscal performance in strengthening economic growth and improving the standard of living of local communities. The intended implication of this study is to offer a policy strategy direction to improve regional fiscal governance in an effort to grow the economy more progressively.